Peningkatan Motivasi Belajar Siswa SMK Tentang Aeronautics Science Melalui Metode Demonstrasi Mini Wind Tunnel di SMK Angkasa 01 Halim Perdanakusuma - Endah Yuniarti; Mufti Arifin; Amat Chaeroni; Syaiful Rifki (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
In the Aviation Vocational High School curriculum, especially in the Physics Subject there is the basic science of Aeronautics, namely Fluid Dynamics. One of the obstacles in studying fluid dynamics is the difficult depiction and the rare props. One of the props that are appropriate and used in the aviation is a wind tunnel. Community service activities in the form of demonstrations and assistance in making mini wind tunnels that have been carried out can be a solution to the problem of misconceptions about fluid dynamics in students of SMK Angkasa 01 Halim Perdanakusuma. The activity was carried out using a survey method regarding the profile of misconceptions about fluid dynamics, demonstration of the Bernoulli principle, and assistance in making a mini wind tunnel. The activity was attended by students of class X and XI which was held from 14 to 20 June 2022 which was divided into 2 (two) sessions, namely a wind tunnel demonstration and assistance in making a mini wind tunnel. Measurement of the level of understanding of Aeronautics Science was carried out 3 (three) times, namely before and after the demonstration and after assisting in the construction of a mini wind tunnel. The result of the first questionnaire is that most of the students have not studied Fluid Dynamics. The results of the second questionnaire were quite significant, where Aeronautics Science knowledge increased after participating in PKM activities. The results of the third questionnaire concluded that there had been a change in the level of Aeronautics Science knowledge of students who took part in making a mini wind tunnel. Keywords: Aeronautics science; Fluid Dynamic; mini wind tunnel;